Pengaruh Konten Pemasaran dan Pemasaran Interaktif terhadap Minat Beli Produk Fashion Generasi Z pada Marketplace Shopee di Kabupaten Aceh Barat - Yusnita Yusnita; Muzakir Muzakir; Cut Mega Putri (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the influence of content marketing and interactive marketing on the buying interest of fashion products among Generation Z on the Shopee marketplace in West Aceh Regency. This research uses a quantitative approach with an associative research design. The population in this study consists of Generation Z consumers who have purchased fashion products through the Shopee marketplace. The sampling technique used purposive sampling with a total sample of 96 respondents. Data were collected through questionnaires using a Likert scale. The data analysis method used was multiple linear regression analysis with the help of SPSS software. The results show that partially, content marketing has a positive and significant effect on buying interest, and interactive marketing also has a positive and significant effect on buying interest in fashion products among Generation Z on the Shopee marketplace. Simultaneously, content marketing and interactive marketing have a positive and significant effect on buying interest. The coefficient of determination (Adjusted R Square) value of 0.725 indicates that 72.5% of the variation in buying interest can be explained by content marketing and interactive marketing variables, while the remaining 27.5% is influenced by other factors outside the research model. The results of this study are expected to provide contributions for business actors in optimizing digital marketing strategies to increase consumer buying interest, especially among Generation Z.